Severe Gingival Recession Caused by Traumatic Occlusion and Mucogingival Stress: A Case Report - Ustun, Kemal; Sari, Zafer; Orucoglu, Hasan; Duran, Ismetdir; Hakki, Sema S (European Journal of Dentistry, 2008)
Gingival recession is displacement of the soft tissue margin apically leading to root surface exposure. Tooth malpositions, high muscle attachment, frenal pull have been associated with gingival tissue recession. Occlusal trauma is defined as injury resulting in tissue changes within the attachment apparatus as a result of occlusal forces. Trauma from occlusion may cause a shift in tooth position and the direction of the movement depends on the occlusal force. We present the clinical and radiological findings and the limitation of periodontal treatment of a severe gingival recession in a case with traumatic occlusion. A 16 years old male, systemically healthy and nonsmoking patient presented to our clinic with severe gingival recession of mandibular canines and incisors. Clinical evaluation revealed extensive gingival recession on the vestibules of mandibular anterior segment. Patient has an Angle class III malocclusion and deep bite. To maintain the teeth until orthodontic therapy and maxillofacial surgery, mucogingival surgeries were performed to obtain attached gingiva to provide oral hygiene and reduce inflammation. After mucogingival surgeries, limited attached gingiva was gained in this case. Regular periodontal maintenance therapy was performed at 2 month intervals to preserve mandibular anterior teeth. Multidisciplinary approach should be performed in this kind of case for satisfactory results. Unless occlusal relationship was corrected, treatment of severe gingival recession will be problematic. For satisfactory periodontal treatment, early diagnosis of trauma from occlusion and its treatment is very important. (Eur J Dent 2008;2:127-133)
Keywords: Severe gingival recession; Malocclusion; Mucogingival surgery